Analisis Daya Dukung dan Efesiensi Pondasi Tanki CPO Kapasitas 1000 Kiloliter Studi Kasus PT.Energi Unggul Persada - Prananda, M. Rizki; Abrar, Aidil; Halimatusadiyah; Marbun, Novri Jenita (SLUMP TeS : Jurnal Teknik Sipil, 2024)
In planning a building construction, several theoretical foundations are needed in the form of structural analysis, knowledge of the strength of materials and other things that are guided by the regulations in force in Indonesia. The aim of this research is to analyze and compare the bearing capacity of group spun pile foundations from the results of field data from the Cone Penetration Test (CPT), Standard Penetration Test (SPT) (using the Aoki and De Alencar Method with the Meyerhof Method), (using the Classical Method) , and compare with the STAADPRO V8i application, as well as calculate the number of uses of spun pile piles and determine the settlement that occurs. Based on the load analysis, the carrying capacity of the D30 group spun pile foundation on a CPO tank with a capacity of 1000 kilo liters based on the method used and field test results data can be, based on CPT/Sondir data (3,694.27), Mayerhof method (2,313.60) , Classic Method(1,783.42), and using the STAAD PRO V8i application (3,132). Based on the analysis carried out in calculating and comparing several methods in determining the number of d30 spun pile piles due to the load acting on the CPO tank structure building with a capacity of 1000 kiloliters, based on the method used and data from field tests, based on maximum Sondir data (36 points with depth 24 meters), Mayerhof Method (26 points with a depth of 24 meters), Kalsik Method (30 points with a depth of 24 meters).